PTH-006 Should we perform colonic polypectomy in patients over 80?. (8th June 2018) - Ahmed, Jabed; Landy, Jonathan
Abstract : Introduction: Previous studies highlight the increased risks attendant with colonoscopy in the elderly population1. Case reports and reviews also suggest avoidance of polypectomy for <2 cm polyps in patients≥85 years 2. We aimed to assess the outcomes of polypectomy in patients≥80 at our trust with five years of follow up. Methods: Colonoscopic data was analysed from the endoscopy reporting system for patients aged ≥80 who had colonoscopy and polypectomy performed in 2011 and 2012. Endoscopy reports, histology reports and patient notes were reviewed. Mortality and cause of death within 5 years of the procedure date were also recorded from the patient mortality coding database. Patients with a synchronous cancer at index procedure were excluded from 5 year colorectal cancer (CRC) mortality analysis. Results: 180 patients (median age 83; range 80–92) were identified with 313 polyps removed. The median ASA grade was 2 (range 1–4) with hypertension, COPD, Cardiac disease and Diabetes the most frequent co-morbidities. 224 (72%) polyps removed were <10 mm in size, 58 (19%) 10–19 mm, 20 (6%)>20 mm (range 20–50 mm) and size was not documented in 9 (3%). In polyps<10 mm in size, 99% had histology showing low grade or no dysplasia. 1% had high grade dysplasia (HGD) and there were no polyp cancers. For polyps 10–19 mm, histology showed low grade or no dysplasia in 81%, HGD in 14% and cancer in 5%. For polyps>20 mm; 30% (6) showed HGD and 5% (1) cancer on histology. There were 3 (1.6%) peri-procedure complications identified (desaturation and bleeding post polypectomy) none requiring admission. 42 (23%) of the patients died within 5 years of the procedure date. The commonest causes of patient mortality were pneumonia, heart failure and stroke. CRC was the cause of death in 1 patient (0.6%) and in this case the index polypectomy was a polyp cancer. Conclusions: The rate of significant complications in patients≥80 undergoing colonic polypectomy is low. However, mortality at 5 years is high in patients≥80 undergoing colonic polypectomy due to co-morbid diseases other than CRC and no significant pathology is seen in diminutive (<10 mm) polyps in this age group. The number of polyps>10 mm in our cohort was small. We would recommend that polypectomy should be avoided for polyps<10 mm in patients≥80 rather than ≥85 as previously suggested and that polypectomy of polyps>10 mm should only be considered after careful deliberation with the patient. References: . Lin OS, et al. Screening Colonoscopy in very elderly patients. The Journal of the American Medical Association 2006;295(20):2357–2365. . Baker G, et al. Learning from adverse outcomes: guidelines on colonoscopic polypectomy in patients aged 85 years and older. Frontline Gastroenterology2016;(7):199–201.